2019
DOI: 10.1029/2019gl083115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ducting on Whistler Mode Chorus or Exohiss in the Outer Radiation Belt

Abstract: Previously published statistics based on Cluster spacecraft measurements surprisingly show that in the outer radiation belt, lower band whistler mode waves predominantly propagate unattenuated parallel to the magnetic field lines up to midlatitudes, where ray tracing simulations indicated highly attenuated waves with oblique wave vectors. We explain this behavior by considering a large fraction of ducted waves. We argue that these ducts can be weak and thin enough to be difficult to detect by spacecraft instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 54 publications
(70 reference statements)
5
54
0
Order By: Relevance
“…Sweep rate, time duration, and maximum amplitudes are calculated for h=5000.3emcnormalΩnormale01, which is approximately equal to 2,500 km or to a magnetic latitude λ m = 5° for L = 4.5. If we measured the maximum amplitudes at larger h , they would grow steadily up to unreasonable values ( B w, max / B eq > 0.1), which is caused by the assumption of parallel propagation of whistler modes, which cannot be justified further from the equator, as was shown by systematic analysis of spacecraft measurements (Santolík et al., 2014) as well as by theoretical considerations of chorus propagation in small ducts (Hanzelka & Santolík, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Sweep rate, time duration, and maximum amplitudes are calculated for h=5000.3emcnormalΩnormale01, which is approximately equal to 2,500 km or to a magnetic latitude λ m = 5° for L = 4.5. If we measured the maximum amplitudes at larger h , they would grow steadily up to unreasonable values ( B w, max / B eq > 0.1), which is caused by the assumption of parallel propagation of whistler modes, which cannot be justified further from the equator, as was shown by systematic analysis of spacecraft measurements (Santolík et al., 2014) as well as by theoretical considerations of chorus propagation in small ducts (Hanzelka & Santolík, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…The existence of Earth‐magnetosphere/ionosphere waveguide is widely accepted, which guides whistler‐mode waves to reach the ground (Ohta et al., 1996; Stenzel, 1999). The most common waveguides are field‐aligned density irregularities (also called density ducts) supported by theoretical and numerical works (Hanzelka & Santolík, 2019; Smith et al., 1960; Streltsov et al., 2006), which have been frequently detected by satellite‐based measurements (Carpenter et al., 2002; Darrouzet et al., 2009) and ground‐based imaging telescope (Loi et al., 2015). Density ducts can guide whistler‐mode waves, which naturally lead to modulations of whistler‐mode wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of all past work on wave propagation modeling, including the recent Hanzelka and Santolík (2019) study, has been based on raytracing and therefore limited to scenarios where density changes slowly over a wavelength. The impact of smaller structures can only be addressed with a full‐wave analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Using cross correlation of observables on multiple spacecraft, Agapitov et al (2011) reported the parameters of plasma density fluctuation scales to be ∼60-100 km transverse to and 1,000-1,500 km along the background magnetic field. Hanzelka and Santolík (2019) investigated the guiding effects of field aligned density irregularities with only 6% density changes. These field aligned irregularities were made narrow in the transverse direction and a key finding was that the presence of such "weak" and "thin" ducts can explain observed wave parameters and such structures are likely more prevalent than previously thought.…”
mentioning
confidence: 99%